A percepção do espaço quandoreferenciado à natureza: pelo olhar do terreiro Dedico - Michela Perigolo Rezende (2009)
This paper sought to point out ways to indicate that the policies adopted for the preservation of heritage in our country have had in the course of our history, great difficulties for a better approach regarding African-Brazilian cultures. We believe this is due mainly to the basic difference, as suggested by many authors, between a view of the world on sacred, religious base, typical of these cultures, and a profane, worldly asceticism view, that would be characteristic of the culture and the modern era. Since such a finding would lead us to understand that there are ways of time and space perception, wich are distinct, especially in regard to the relationship man / nature. In order to enlight and give support to research which refers to the spatial vision of the African-Brazilian traditional culture, it was decided to take the study case Terreiro DeDiCo The Awakening of the Divine Consciousness.